A slice of hygiene: justification and consequence in the persuasiveness of prescriptive and proscriptive signs. (1st October 2016) - Leoniak, Krzysztof Jan; Maj, Konrad
Abstract: Studies concerning sign effectiveness highlight the use of justifications and information about consequences of non-compliance. Assuming that the most persuasive messages contain both types of information, we compared the effectiveness of eight different signs (that encouraged supermarket shoppers to hygienically handle bread). The independent variables were (a) sign content (justification vs. consequence vs. justification and consequence vs. neutral) and (b) form of request (prescriptive vs. proscriptive). After assessing the subjective level of the signs' persuasiveness through a survey ( N = 240), we observed people's compliance in a natural experiment ( N = 1.440). Signs containing both a justification and information about consequences achieved the highest rating and actual compliance.